A sample assessment of records management practices in the University of the Philippines toward a development of a self-audit tool - Comia, Rechelle Olaguer (2015)
For more than a hundred years as the leading university in the Philippines, the University of the Philippines (UP) has long struggled in managing its records. A number of studies on records management in the University confirm and illustrate this. The results of the assessment and self-audit conducted in this study, through the best practices of ISO 15489 and RA 9470, also suggest that same observation.